Optimization of solid-state fermented corn distillers dried grains with solubles: effects on growth performance and tissue morphology in broiler chickens - Peng, Yuqing; Wang, Mengchen; Zheng, Zewei; Wang, Lei; Zhang, Xuelei; Cheng, Kang; Zhang, Yong (Frontiers in Animal Science, 2024)
In recent years, the use of corn DDGS has alleviated the problem of protein feed shortages to a certain extent; however, its high mycotoxin content seriously restricts its application in feedstuffs. In this study, the conditions of solid-state fermented corn DDGS were optimized to investigate changes in the nutrient composition of solidstate fermented corn DDGS and their effects on the growth performance and histological section of yellow-feathered broilers. The optimal strain ratio for solidstate fermentation was determined by orthogonal testing as 1:1:2 for B. desmois JA3:B. subtilis ANSB01G: and B. subtilis ANSB060, and the response value was the score of the degradation rate of Deoxynivalenol (DON), zearalenone (ZEN), and aflatoxin B1 (AFB1) weighted by 4:4:2. Optimal conditions for the solid-state fermentation of maize DDGS were determined by B-Behnken response surface design:the inoculum amount was 1%, the feed to liquid ratio was 1:1.25, the fermentation temperature was 37°C, and the fermentation time was 29.5 h. The optimal conditions for solid-state fermentation of maize DDGS were as follows: the inoculum amount was 1%, the material-liquid ratio was 1:1.25, the fermentation temperature was 37℃, the fermentation time was 29.5h, and the degradation rates of DON, ZEN, and AFB1 in the fermented maize DDGS were 81.6%, 55.18%, and 41.14%, respectively. Moreover, solid-state fermentation significantly improved the nutrient content, in which the amounts of amino acids, crude ash, and crude fat were significantly increased (P < 0.05) and the content of crude fiber was significantly decreased (P < 0.05). The in vitro digestibility of dry matter, crude protein and crude fiber increased significantly (P < 0.05); in addition, compared with the control group, the addition of fermented maize DDGS significantly increased the daily calorific intake of broiler chickens, the daily weight gain (P < 0.05); heart, liver and intestinal tissues underwent no obvious pathological changes.